On reputation: a microfoundation of contract enforcement and price rigidity - Ernst Fehr; Martin Brown; Christian Zehnder (Institute for the Study of Labor (IZA), 2008)
We study the impact of reputational incentives in markets characterized by moral hazard problems. Social preferences have been shown to enhance contract enforcement in these markets, while at the same time generating considerable wage and price rigidity. Reputation powerfully amplifies the positive effects of social preferences on contract enforcement by increasing contract efficiency substantially. This effect is, however, associated with a considerable bilateralisation of market interactions, suggesting that it may aggravate price rigidities. Surprisingly, reputation in fact weakens the wage and price rigidities arising from social preferences. Thus, in markets characterized by moral hazard, reputational incentives unambiguously increase mutually beneficial exchanges, reduce rents, and render markets more responsive to supply and demand shocks.
urn:nbn:de:101:1-20080828211
Keywords: D82; 330; Reputation; reciprocity; relational contracts; price rigidity; wage rigidity; Unvollständiger Vertrag; Prestige; Austauschtheorie (Soziologie); Marktmechanismus; Preisrigidität; Lohnrigidität; Mikroökonomische Fundierung; Theorie